Family Tax Splitting: A Microsimulation of its Potential Labour Supply and Intra-household Welfare Effects in Germany - François Laisney; Denis Beninger; Miriam Beblo (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
This paper assesses the effects that an introduction of the French family splitting mechanism would have on German families' labour supply and intra-household consumption behaviour. We use simulated real world microdata created by means of a 'deterministic' collective labour supply model. The data are generated by a compound procedure of estimation and calibration based on GSOEP data. In a microsimulation the present tax-benefit system with child benefit/allowance is replaced by a tax scheme with family splitting. The resulting changes in labour supply are surprisingly small, even for women. Welfare effects are also modest, but differ for husbands and wives.
Keywords: D11; J22; D12; D13; D31; J12; 330; Collective model; household labour supply; intra-household allocation; tax reform; family splitting; Familienbesteuerung; Steuerreform; Steuerwirkung; Arbeitsangebot; Haushaltsproduktion; Simulation; Deutschland; Mikrosimulation